Resumptive Streptococcus mutans Persisters Induced From Dimethylaminododecyl Methacrylate Elevated the Cariogenic Virulence by Up-Regulating the Quorum-Sensing and VicRK Pathway Genes - Lu, Junzhuo; Cheng, Lei; Huang, Yuyao; Jiang, Yaling; Chu, Chun-Hung; Peng, Xian; Li, Mingyun; Xu, Hockin H. K.; Zhou, Xuedong; Ren, Biao (Frontiers in Microbiology, 2020)
Bacterial persistence has become a worldwide health problem due to its ability to cause the recalcitrance and relapse of infections. The existence of bacterial persistence and their possible mechanisms have been widely reported. However, the following regrowth of persister cells in not clear although the awakening of dormant surviving persisters is the key to reinitialize bacterial infection. In this study, we investigated the growth character and cariogenic virulence during the recovery of Streptococcus mutans drug-tolerant persister cells induced by a novel quaternary ammonium: dimethylaminododecyl methacrylate (DMADDM). A remarkable lag phase was observed in S. mutans persisters when regrew at the first 24 h compared to normal cells. During the entire recovery state, persisters are metabolically active to increase the production of both water-soluble and water-insoluble glucan. The shortage of cell number in persisters resulted in the decrease of lactic acid production, but persisters gradually recovered the normal acid production ability after 72 h. The up-regulated expression of gtf and vicR were in line with comDE circuit and consistent with the virulence change during the regrowth stage. Our findings proved that lethal dosages of DMADDM induced drug-tolerant S. mutans persisters in biofilm, which had a prolonged lag phase and elevated cariogenic virulence during regrowth. The recovery and elevated virulence of persisters were regulated by quorum-sensing and VicRK pathway. This alarmed the elevated cariogenicity of persisters and highlighted the critical requirement for the drug-tolerance evaluation when developing new oral antimicrobial agents. To the best of our knowledge, we characterized the regrowth and cariogenic virulence variation of S. mutans persisters induced by quaternary ammonium for the first time. Our findings suggest that S. mutans persisters with the elevated cariogenic virulence during their regrowth stage highlighted the need of new strategy to overcome bacterial persistence. Meanwhile, the prolonged lag phase and the involvement of quorum-sensing system in the regrowth of S. mutans persisters may provide the potential targets.